Subjective cognitive complaints and blood biomarkers of neurodegenerative diseases: a longitudinal cohort study - Perna, Laura; Stocker, Hannah; Burow, Lena; Beyer, Léon; Trares, Kira; Kurz, Carolin Isabella; Gürsel, Selim; Holleczek, Bernd; Tatò, Maia Lucia; Beyreuther, Konrad; Mons, Ute; Gerwert, Klaus; et al. (Alzheimer's research & therapy, 2023)
Subjective cognitive complaints (SCC) have been mostly studied in the context of Alzheimer’s disease in memory clinic settings. The potential of combining SCC with genetic information and blood biomarkers of neurodegenerative diseases for risk assessment of dementia and depression in the absence of dementia among community-dwelling older adults has so far not been explored.